REPROCESSING OF POLYETHYLENE TEREPHTHALATE GLYCOL COPOLYMER IN THE ADDITIVE MANUFACTURING PROCESS - ЯЩУК, Є. С.; СОВА, Н. В.; СЛЄПЦОВ, О. О.; ФЕДОРІВ, Т. Р.; ОСАУЛЕНКО, С. І. (Technologies and Engineering, 2023)
Purpose. Study of the properties of PET copolymer during close loop recycling by the additive manufacturing. Methodology. The main physical and mechanical properties of the test samples were determined – strength and relative elongation at break according to ISO 527-2:2012, modulus of elasticity during bending – BS EN ISO 178:2003, density according to ISO 1183-1:2019. The determination of the melt flow index of the composites was carried out in accordance with ISO 1133-1:2011 on a capillary viscometer of constant pressure at a temperature of (250±0.5)°C and a cargo weight of 2.16 kg. Findings. Polyethylene terephthalate copolymer waste produced during additive manufacturing is characterized by high uniformity and does not contain impurities of other materials, which positively affects the mechanical properties of secondary raw materials. The choice of extrusion temperature during the setting of additive manufacturing parameters is determined by the value of the melt flow rate of the polymer material. Preliminary drying of the polymer monofilament provides a more monolithic product under the condition of increased extrusion temperature, compared to the conditioned monofilament. The type of filling during additive manufacturing significantly affects the final mechanical properties of the finished product. Filling 90º allows you to obtain products with the highest mechanical characteristics, which is due to the realization of the effect of orientational stretching of the polymer melt and ordering of its supramolecular structure. Originality. It was established that the maximum values of mechanical characteristics in the test sample with PET-G are achieved with the type of filling of 90º during the preliminary drying of the monofilament, which is due to the effect of orientational drawing during the additive production of the sample. Practical value. The possibility of reprocessing waste from the additive production of polyethylene terephthalate copolymer into finished products without a significant decrease in their mechanical characteristics has been established.